Radiological evaluation of response in patients with locally advanced/metastatic soft tissue sarcoma treated with trabectedin - Ceddia, S.; Onesti, C. E.; Vari, S.; Torchia, A.; Cosimati, A.; Riva, F.; Maccallini, M. T.; Cerro, M.; Benvenuti, G.; Russillo, M.; Anelli, V.; Sperduti, I.; et al. (Frontiers in Pharmacology, 2024)
Trabectedin is an antineoplastic drug approved for patients (pts) with advanced soft tissue sarcomas (STS). Interestingly, the radiological evaluation of response during trabectedin therapy is peculiar.The aim of this single-center retrospective study is to analyse the concordance of response assessment according to RECIST compared with Choi criteria, in patients with STS treated with trabectedin between 2009 and 2020 at Regina Elena National Cancer Institute in Rome.We are presenting the preliminary data collected in the last two months (mos) on 37 pts who received the diagnosis between 2015 and 2020, with median age of 52.5 years (range 32-78). Median number of trabectedin cycles administered was 4 (range 2-50), for a median follow up of 5.83 mos (range 1-60). Histological subtypes of STS were: 5 (13.5%) leiomyosarcoma, 14 (37.8%) liposarcoma, 9 (24.3%) undifferentiated pleomorphic sarcoma, 3 (8.1%) synovial sarcoma, 6 (16.2%) other rare histological subtypes. Eight pts (21.6%) received trabectedin in the first line setting, 21 pts (56.8%) in second line, 7 pts (18.9%) received it in subsequent lines. One pt received trabectedin as neoadjuvant therapy in a clinical trial (ISG-STS 1001). The median progression-free survival was 3.6 mos (CI95% 2.7-4.6); the median overall survival was 34.3 mos (CI95% 0-75.4). The radiological responses were evaluated with both RECIST and Choi criteria: in 33 pts (89.2%) responses matched; whereas in 4 pts (10.8%) did not match. The best responses obtained according to RECIST criteria were: 2 (5.4%) partial response (PR), 13 (35.1%) stable disease (SD) and 22 (59.5%) progressive disease (PD). Instead, 2 (5.4%), 13 (35.1%) and 22 (59.5%) pts obtained PR, SD and PD respectively, according to Choi criteria. Cohen's kappa coefficient of concordance was 0.792 (pvalue < 0.002). A specialized radiologist performed all the imaging examinations using a dedicated workstation in the same center.In this first analysis, the concordance between RECIST and Choi assessments demonstrates no statistically significant difference. Anyway, responses did not match for 4 pts. We are expanding the analysis to all of the pts included in the original cohort to confirm or deny these initial results.